LDPC codes from cubic semisymmetric graphs - Crnković, Dean (Ars mathematica contemporanea, 2022)
In this paper we study LDPC codes having cubic semisymmetric graphs as their Tanner graphs. We discuss the structure of the smallest absorbing sets of these LDPC codes. Further, we give the expression for the variance of the syndrome weight of the constructed codes, and present computational and simulation results.
Keywords: cubic graph; kubičen graf; LDPC code; LDPC koda; semisimetričen graf; semisymmetric graph